Cell death programs in Yersinia immunity and pathogenesis - Philip, Naomi H.; Brodsky, Igor E. (Frontiers in Cellular and Infection Microbiology, 2012)
Cell death plays a central role in host-pathogen interactions, as it can eliminate the pathogen’s replicative niche and provide pro-inflammatory signals necessary for an effective immune response; conversely, cell death can allow pathogens to eliminate immune cells and evade anti-microbial effector mechanisms. In response to developmental signals or cell-intrinsic stresses, the executioner caspases-3 and -7 mediate apoptotic cell death, which is generally viewed as immunologically silent or immunosuppressive. A proinflammatory form of cell death that requires caspase-1, termed pyroptosis, is activated in response to microbial products within the host cytosol or disruption of cellular membranes by microbial pathogens. Infection by the bacterial pathogen Yersinia has features of both apoptosis and pyroptosis. Cell death and caspase-1 processing in Yersinia-infected cells occur in response to inhibition of NF-κB and MAPK signaling by the Yersinia virulence factor YopJ. However, the molecular basis of YopJ-induced cell death, and the role of different death pathways in anti-Yersinia immune responses remain enigmatic. Here, we discuss the role that cell death may play in inducing specific pro-inflammatory signals that shape innate and adaptive immune responses against Yersinia infection.